新世代電阻式非揮發性記憶元件之製作與特性研究 - 曾俊元; TSENG TSEUNG-YUEN (My University, 2008)
因鈦酸鉍薄膜之電阻值可經由施加電壓作改變，且藉由不同電阻值去儲存資料。在 此三年期研究計畫中，將研究開發鈦酸鉍薄膜作為雙穩態電阻層之非揮發性記憶體。在 第一年與第二年的計畫中，將利用射頻磁控濺鍍法來製造記憶體薄膜；調整不同製程參 數、參雜物質、表面處理並搭配多種上下電極組合以期獲得合適的憶體薄膜之製程條件 及結構。此外將分析量測上述記憶體薄膜之晶體結構、組合成分、物理特性與電學性質； 歸納這些分析結果以進一步瞭解雙穩態電阻轉態機制與高可靠度之最佳化製程條件。第 三年的研究中，將實現電阻式記憶體在不同電路結構中，如整合一個雙穩態電阻轉態結 構至標準互補式金氧半電晶體製程(CMOS process)；並搭配一個存取電晶體或二極體 作為一組記憶體晶包，抑或以記憶陣列(memory array)均可實現電路結構。以上述結構 測試一些記憶體標準規格，例如資料記憶力(data retention)、耐久度(endurance)、非破 壞性讀取測試(non-destructive readout)及高溫可靠度，期許能將此研究實現於非揮發性 記憶體或嵌入式記憶體之應用。

The resistance of the Bi4Ti3O12 thin film can be varied by applying voltage bias, so that the data storage can be achieved by different resistance values of Bi4Ti3O12 thin film. In this three-year research project, Bi4Ti3O12-based memory thin films will be deposited as the bistable resistive switching layer for nonvolatile memory application. In the first two years, Bi4Ti3O12-based memory thin films will be fabricated by radio-frequency magnetron sputtering. Various processing treatments including tuning different parameters of fabrication process, dopants, surface treatments, thermal treatments, and the combinations of various top and bottom electrodes will be employed to make the Bi4Ti3O12-based memory thin films more suitable for nonvolatile memory application. Moreover, the crystal structures, the chemical compositions, the physical and electrical properties of the Bi4Ti3O12-based memory thin films will be analyzed and characterized for clearly understanding the resistive switching mechanism and further modifying the fabrication process for obtaining high quality and high reliability films. In the third year, the Bi4Ti3O12-based memory will be integrated into circuit level. The memory array, the access transistor and the access diode will be adapted to implement the Bi4Ti3O12-based memory cells to investigate the possibility of practical application of nonvolatile memory. Besides, the electrical properties such as retention time, endurance and non-destructive readout, and the reliability tests will also be performed for nonvolatile memory and embedded memory applications.
Fabrication and Characteristics of Novel Resistive Nonvolatile Memory
Keywords: 鈦酸鉍; 電阻式隨機存取記憶體; 非揮發性記憶體; 鈣鈦礦結構; 電阻轉換機制; 導電機制; Bi4Ti3O12; resistive random access memory (RRAM); nonvolatile memory; perovskite structure; resistive switching mechanism; conduction mechanism.